In vitro antioxidant, anti-diabetic, anti-inflammatory, and wound-healing properties of Mitragyna speciosa (korth.) havil. methanolic extract - Zailan, Nur Fatin Zalikha (2022)
Diabetes mellitus (DM) occurs as the consequence of the destruction of insulinproducing pancreatic beta (β)‐cells (type 1 DM) or cell resistance to insulin (type 2 DM). Infections with a slow rate of wound healing are commonly observed in patients with DM. Diabetic foot ulcer is a common complication of DM which imposes high costs for its treatment and management. Chronic wounds in diabetes are associated with impaired angiogenesis, leukocyte function, and fibroblast proliferation. Plant-based remedies such as Mitragyna speciosa (M. speciosa) have been used by local people in Malaysia as a complementary treatment for various illnesses including lowering blood glucose in diabetic patients. This study aims to determine the in vitro antioxidant, anti-diabetic, anti-inflammatory, and wound-healing properties of M. speciosa methanolic extract (MSME). The screening of phytochemical compounds in MSME was performed by ultra-high-performance liquid chromatography coupled with traveling-wave ion mobility spectrometryquadrupole time of flight mass spectrometry (UHPLC-TWIMS-QTOF-MS/MS) analysis. The antioxidant content and scavenging activity of MSME were evaluated by total phenolic content (TPC) assay and total flavonoid content (TFC) assay along with 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. In addition, the cytotoxicity effects of MSME on RAW264.7 macrophages cells and 3T3-L1 fibroblast cells together with the antioxidative effect of MSME against oxidative stress in hydrogen peroxide (H2O2)-induced 3T3-L1 cells were determined by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2- (4-sulfophenyl)-2H-tetrazolium (MTS) assay. The anti-diabetic properties of MSME were studied by measurement of α-amylase enzyme inhibition. Besides, the glucose uptake activity of MSME was determined by the median fluorescence intensity (MFI) of 2-NBDG in 3T3-L1 cells. Anti-inflammatory properties of MSME were determined in LPS-stimulated RAW264.7 cells through secretion of inflammatory mediators including nitric oxide (NO) and cytokines by Griess assay and cytometric bead array (CBA), respectively. The ability of MSME in accelerating cell migration and wound closure was investigated on 3T3-L1 cells by scratch assay. The phytochemical compounds identified in MSME (100 mg/mL) include rutin, epicatechin, quercetin, procyanidin B2, and chlorogenic acid. MSME (1 mg/mL) has lower Total Phenolic Content (TPC) than positive control Pterostilbene (Ptb) (MSME: 167.43±13.50 mg GAE/g sample and Ptb: 230.52±10.92 mg GAE/g sample) but high in TFC (MSME: 347.72±15.97 mg QE/g sample and Ptb: 212.73±17.92 mg QE/g sample). MSME showed relatively similar antioxidant scavenging activity (IC50=4.34 μg/mL) with Ptb (IC50=4.39 μg/mL) in the DPPH assay. Conversely, in the ABTS assay, MSME showed lower antioxidant scavenging activity (IC50=4.25 μg/mL) than Trolox and Ptb (IC50=1.50 and 1.56 μg/mL, respectively). MSME (25, 50, and 100 μg/mL) did not show any toxicity effect on cell survival and protected 3T3-L1 cells from oxidative damage by H2O2. Increased inhibition of α-amylase activity (46.39±4.43%) and glucose uptake (MFI: 274.00±8.00) were detected in the 100 μg/mL of MSME suggesting anti-diabetic activity of MSME. MSME was also found to have antiinflammatory activity through the suppression of NO and cytokine levels in LPS-stimulated RAW264.7 cells. In addition, MSME also induces wound closure in 3T3-L1 cells by accelerating cell migration. MSME may increase glucose uptake, downregulate inflammatory responses of macrophages and subsequently accelerate the process of wound repair which shows promising antioxidant, anti-diabetic, anti-inflammatory, and wound-healing properties. Thus, further study should be conducted to recommend M. speciosa as a possible treatment for DM and wound healing.